CART peptide following social novelty in the prairie vole (Microtus ochrogaster) - Hostetler, Caroline M. (2011)
Prairie voles (Microtus ochrogaster) are monogamous rodents that display high levels of affiliative behaviors, including pair-bonding, biparental care, and cooperative breeding. Species differences in basal cocaine- and amphetamine-regulated transcript (CART) mRNA and peptide expression have been found between prairie voles and polygamous meadow voles. Therefore, we hypothesized that the CART system may play a role in the regulation of social behavior in this species. Male and female adult prairie voles were placed in a cage either alone, or with a novel social partner of the same or opposite sex. After 45 minutes, subjects were sacrificed and CART peptide expression was examined using immunohistochemistry. We examined fifteen hypothalamic, limbic, and hindbrain regions of interest, focusing on areas that show species-specific patterns of expression. We found that subjects paired with a novel conspecific had lower levels of peptide in the bed nucleus of the stria terminalis (BNST) than isolated animals. This may reflect increased peptide release following increased dopaminergic activity in animals exposed to a novel conspecific. Additionally, CART peptide was higher in the nucleus accumbens (NAc) of subjects paired with an opposite sex partner compared to those paired with a same-sex conspecific, although there was no difference between isolated subjects and either socially housed group. These findings suggest that CART in the NAc is differentially responsive to the sex of adult conspecifics and that the social environment influences CART expression in the prairie vole in a region- and stimulus-specific manner.